A fotomontagem vanguardista e suas novas formas : um estudo sobre a manipulação fotográfica e seu uso na arte - Marinho, Renata Cardoso (2019)
Aiming to explore plastically manipulated photography, this study intends to argue photographic-philosophic concepts such as manipulation, reality, simulation, index, acting, materiality and reproducibility in order to learn more about the images upon which we concentrate the research. We analyze the changes in Art based on which the worship value is replaced by the exposition value creating a new way to appreciate, create and study Art. Based on these concepts we investigate manipulations on photography from the following artistic movements: Pictorialism and its search for an artistic statute for photographic imagery through the pictorial changes on the negatives; Russian Constructivism and its application on the Russian Revolution as the Soviet state’s advertising tool, and as critique to the Nazi party; Dadaism, which rises during the interwar period in Europe, based on chaos and disorder, taking down the traditional ways of art with sarcasm; Surrealism, which began with Breton , the writer, and also took inspiration on Freud’s insights on psychoanalysis and the awakening of the primitive unconscious of men; comparing the results obtained from analog processes utilized by these vanguards to Photoshop, a computer software which modifies photographic images through its available functions and digital tools, in order to prove that the creative processes utilized by the vanguards through analog technology were emulated by Photoshop tools. Based on what was already known, the form of modifying images was emulated on the software to facilitate its use and to promote its commercialization. Processes that took a long amount of time to elaborate according to the artist’s intent and the objectives of the movement, along with the high cost (in the past) demanded for the acquisition of the necessary materials, now start to be reproduced in a computer’s interface in a short amount of time, utilizing only keyboard shortcuts. The possibilities were multiplied, attending to the artistic needs of the digital society, where the outcome must be synchronized with the landmarks of the contemporary culture.